A Mobile Extracorporeal Extremity Salvage System for Replantation and Transplantation. Issue 3 (March 2016) - Kueckelhaus, Maximilian; Fischer, Sebastian; Sisk, Geoffroy; Kiwanuka, Harriet; Bueno, Ericka M.; Dermietzel, Alexander; Alhefzi, Muayyad; Aycart, Mario; Diehm, Yannick; Pomahac, Bohdan
Abstract : Background: Traumatic amputation is the second leading cause of limb loss in the United States. The preferred treatment is salvage and replantation of the amputated limb, whenever possible, and allotransplantation is a novel procedure whereby healthy limbs are procured from deceased organ donors and transplanted into the amputee recipient. A major restriction for both procedures is the irrecoverable muscle damage occurring due to ischemia. We investigated the feasibility of using a novel lightweight, mobile perfusion device specifically designed to perfuse amputated porcine limbs with an acellular perfusion solution to delay ischemic muscle damage prior to transplantation or replantation. Methods: Bilateral hind limbs of Yorkshire pigs were amputated; one of the limbs was preserved by perfusion in the mobile perfusion device, and the other by storage in ice slurry for 12 hours. Results: Five sets of bilateral limbs were preserved as described previously. A defined pressure of 30 mm Hg was reliably maintained in the arterial system without loss of flow. Comparison of the perfusate composition before and after limb passage revealed significant differences. Muscle biopsies showed a consistent progression of clusters of hypoxic cells in the control limbs with time. Similar changes could not be observed in the perfused tissue. Conclusions: We have designed and built a small, mobile perfusion device that is operational and that more closely mimics the normal physiological environment when compared with the current standard of preservation in ice slurry. This project may have far-reaching implications for the treatment of limb loss through replantation and transplantation.